2015
DOI: 10.2298/pif1502085g
|View full text |Cite
|
Sign up to set email alerts
|

Biology and harmfulness of Brassica pod midge (Dasineura brassicae Winn.) in winter oilseed rape

Abstract: SUmmARyThe Brassica pod midge (Dasineura brassicae Winn.) is an important pest in oilseed rape (Brasica napus L.). It develops two generations per year and overwinters in the larval stage in cocoons in soil. Immigration of the first generation adults lasted from the beginning of April until the end of May. Larvae developed in pods from mid-April to mid-June, causing pod deformation and cracking, which resulted in premature falling out of seeds and yield reduction. Pod damage amounted to 11.6%. The emergence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“… Todorov et al (2022) provide a list of parasitoid species found in oilseed rape fields in Bulgaria with comments on perspectives for biological control, but only for the family Pteromalidae . Oilseed rape pests, on the other hand, are relatively well studied in Serbian fields from both taxonomical and traditional chemical management aspects ( Kereši et al 2007 , Sekulić and Kereši 2007 , Štrbac et al 2007 , Mitrović et al 2008 , Milovac et al 2010 , Graora et al 2013 , Milovanović et al 2013 , Graora et al 2015 , Sivčev et al 2015 , Sivčev et al 2016 , Milovac 2016 , Marjanović and Prodanović 2021 ). Similarly, the parasitoid wasp fauna of other crops in Serbia, especially cereals and alfalfa, has also been well studied ( Tomanović et al 2003 , Kavallieratos et al 2004 , Kavallieratos et al 2005a , Kavallieratos et al 2005b , Tomanović et al 2008 , Žikić et al 2012 , Tomanović et al 2021 ), but currently, there is a gap in knowledge of the parasitoid wasp fauna in oilseed rape.…”
Section: Introductionmentioning
confidence: 99%
“… Todorov et al (2022) provide a list of parasitoid species found in oilseed rape fields in Bulgaria with comments on perspectives for biological control, but only for the family Pteromalidae . Oilseed rape pests, on the other hand, are relatively well studied in Serbian fields from both taxonomical and traditional chemical management aspects ( Kereši et al 2007 , Sekulić and Kereši 2007 , Štrbac et al 2007 , Mitrović et al 2008 , Milovac et al 2010 , Graora et al 2013 , Milovanović et al 2013 , Graora et al 2015 , Sivčev et al 2015 , Sivčev et al 2016 , Milovac 2016 , Marjanović and Prodanović 2021 ). Similarly, the parasitoid wasp fauna of other crops in Serbia, especially cereals and alfalfa, has also been well studied ( Tomanović et al 2003 , Kavallieratos et al 2004 , Kavallieratos et al 2005a , Kavallieratos et al 2005b , Tomanović et al 2008 , Žikić et al 2012 , Tomanović et al 2021 ), but currently, there is a gap in knowledge of the parasitoid wasp fauna in oilseed rape.…”
Section: Introductionmentioning
confidence: 99%